„Wojciechowym szlakiem” Gertrudy Skotnickiej na tle innych opowieści o świętym Wojciechu dla młodego czytelnika - Olszewska, Bożena (Stylistyka, 2020)
The novel Wojciechowym szlakiem [On the Trail of St Adalbert] by Gertura Skotnicka stands out from other hagiographic works about this saint not only in terms of its size, but also as far as its composition and method of presenting this character are concerned. In contrast, the works by Ewa Skarżyńska and Andrzej Hartliński do not go beyond the established genre formula. Only Anna Czerwińska-Rydel uses an original idea, implementing in her story the motif of the Gniezno Doors. The content of each bas-relief scene visible on the door constitutes a separate chapter of the book. Skotnicka also refers to this motif by mentioning its artistic value in the account of a high school student and the narrator, and by using it as illustrative material for her book. The author plays with time to transfer the boy-hero into the 10th century, which allows her to slowly create a double portrait: conventional, i.e. of an idealised saint and martyr, and the other one – of an ordinary man. This way of portraying creates plenty of room for active participation of the reader, stimulating their imagination. The artistic consequence is a multi-layered narrative, the use of a story within a story, and a play with genre and stylistic conventions. The diversity of linguistic and stylistic forms seems to be motivated by the course of action, changing the setting and time, the situation in which the boy-hero takes part, and the presence of two world-views: Christian and pagan.